How Is The Attitude Towards English? Indonesian Vocational High School Students’ Experiences - Ata Suryata; Mobit Mobit; Dedeh Kartini (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Language attitude takes a pivotal role in their language learning practice. This research aims to investigate the students' attitude toward English as supporting language at vocational high school context and describe the impacts of the attitude toward English. The data was collected through observation, questionnaire and open-minded interviews. Six 12th grade students participated in this research. The analysis was carried out through data reduction, display and verification. The findings revealed that the students believed in their future carrier they need English. as tools to compete in work field later. The conclusion is students’s attitude towards English for supporting language in studying at vocational high school is positif in each component of attitude. Beside that, the impact of students’ attitude towards English for vocational high school are lack of serious and have a problem in self-confidence. It could be seen during the learning process some students face difficulties in learning English and they are also feel nervous and afraid to make mistakes when they were asked by the teacher to speak. This research is expect to help the researcher and able to useful in develpoing the next research from the other aspect towards English.